Pengembangan Bahan Ajar Guru Pada Mata Pelajaran Akhlak Kelas IV di Madrasah Diniyyah Takmiliyah Awaliyah Masjid Agung Ashliyah - Nurasyiah Nurasyiah; Taufik Rahman; Diana Sartika (Concept: Journal of Social Humanities and Education, 2024)
Madrasah Diniyah Takmiliyah Awaliyah was one of the non-formal education in Indonesia, however there are several problems in learning at MDTA such as those found in moral learning at MDTA Masjid Agung Ashliyah Padang Panjang, namely teacher textbooks in teaching have not met learning objectives because the material is still limited and incomplete, the books provided by the madrasah are also still limited and teachers have not used teaching tools in the form of lesson implementation plans (RPP) in the learning process, so that the learning process is less effective and efficient. This study aims to produce a product in the form of teacher teaching materials as a guide for teachers in teaching. This study is entitled "Development of Teacher Teaching Materials for the Subject of Morals for Class IV at MDTA Masjid Agung Ashliyah Padang Panjang". This type of research was Research and Development (R&D) using the 4D model, namely Define, Design, Develop, Disseminate, but this research only goes as far as Develop. This research was conducted at MDTA Masjid Agung Ashliyah Padang Panjang from May 10 to August 5, 2024. This study focuses on research on the development of teacher teaching materials for the subject of morals for class IV MDTA on the material "Morals are Easy for Fellow Humans". After the development of the teacher teaching materials, a feasibility test was carried out by curriculum experts and media experts. The results of the curriculum feasibility test were 86% with very feasible criteria, while the results of the media feasibility test were 84% with very feasible criteria, while the response of the morals subject teacher to the development of this teacher teaching material was 89.4% with a statement of very feasible. So it can be concluded that the development of teacher teaching materials for the subject of morals is very feasible to use.